Designing pictorial symbols - Holmes, Nigel; De Neve, Rose (Watson-Guptil, 1985)
Presents in practical, easy-to-follow steps, the conceptual thinking and artistic follow through needed to create effective pictorial symbols.
Keywords: Holmes, Nigel <1942->; Psychologie; Graphic arts -- Technique; Signs and symbols -- Psychological aspects; Design; Piktogramm; Grafikdesign; Zeichen